Introductory reflections on logic and lacanian theory (Psicologia USP, 2004)
In the course of his teaching, Lacan not only made reference to Logic theorists such as Frege and Russel but also extracted from Logic the foundation to formalize psychoanalysis. Why does Lacan resort specificaly to Logic in order to transmit psychoanalysis? What are the relations between Modern Logic and the psychoanalytical experience? This article aims to offer a first approach to these questions